Detection, distribution, and functions of RNA N6-methyladenosine (m6A) in plant development and environmental signal responses - Xiang, Yang; Zhang, Dian; Li, Lei; Xue, Yi-Xuan; Zhang, Chao-Yang; Meng, Qing-Feng; Wang, Jin; Tan, Xiao-Li; Li, Yu-Long (Frontiers in Plant Science, 2024)
The epitranscriptomic mark N6-methyladenosine (m 6 A) is the most common type of mRNA post-transcriptional modification in eukaryotes. With the discovery of the demethylase FTO in mammals, this modification has been proven to be dynamically reversible. As technology has advanced, research on m 6 A modification in plants has also rapidly developed. m 6 A modification is widely distributed in plants, usually enriched near stop codons and 3'-UTRs, and has conserved modification sequences. The related proteins of m 6 A modification mainly consist of three components: methyltransferases (writers), demethylases (erasers), and reading proteins (readers). In plants, m 6 A modification mainly regulates plant growth and development by modulating RNA metabolic processes and plays an important role in responding to environmental signals. In this review, we briefly outline the development of m 6 A modification detection techniques, comparatively analyze the distribution characteristics of m 6 A in plants, summarize the methyltransferases, demethylases and binding proteins related to m 6 A, elaborate on how m 6 A modification functions in plant growth, development and response to environmental signals, and provide a summary and outlook on the research of m 6 A in plants.